Oceanography / The Last Frontier - Vetter Richard C (Voice Of America, 1974)
Introduction, The History of Oceanography, The Birth and Growth of the Oceans, Chemical Cycles in the Sea, The Marine Chemistry of Carbon and Its Role in Oceanographic Research, Marine Manganese Minerals, Trace Elements in the Oceans, The Origin and Growth of the Ocean Basins, The Ocean Sediments as Keys to the Past, Scientific Drilling in the Deep Oceans, Minerals from the Sea, Unrest in the Deep Sea, Waves, Tides, The Great Alaskan Tsunami, Deep Ocean Circulation, Atmoshere and Oceans, Upwelling and the Moonsoons, Processes of Air-Sea Interaction, The Origin and Evolution of Life in the Sea, Productivity of Organic Matter in the Oceans, The Food Web of the Sea, Fisheries of the World, The Multiple Use of the Coastal Environment, Shore Processes, Fishery Forecasting for Food From the Sea, Circulation and Mixing in Coastal Regions and Estuaries, International Cooperation, The Future.